The Justices of the Peace 1679 - 1760. - Landau, Norma (University of California Press, 2022)
In the eighteenth century the justices of the peace governed England. While Parliament debated questions of trade, taxation, and foreign policy, the justices administered England's internal affairs. So powerful were the later Stuart and early Hanoverian justices that they were virtually independent, and it is their independence which makes them fascinating. Neither the central government nor Parliament told them what to do, closely supervised their activity, o.
Description based upon print version of record.
Keywords: Justices of the peace -- England -- History.; Juges de paix -- Angleterre -- Histoire.; Justices of the peace.; England.; History.